Reciprocal of the Reciprocal
Let a , b be positive real numbers. Set x 0 = a and x n + 1 = ( x n 1 + b ) 1 for n 0 .
  • Prove that x n is strictly monotone decreasing.
  • Prove that the limit exists and find it.

For the induction step we'll notice before anything else that in general for any n N 1 we have that x n + 1 = ( x n 1 + b ) 1 = 1 1 x n + b = 1 1 + b x n x n = x n 1 + b x n moving on, let k N 1 we'll prove that x k x k + 1 , x k + 1 = x k 1 + b x k = x k 1 1 + b x k 1 1 + b ( x k 1 1 + b x k 1 ) = x k 1 1 + b x k 1 ( 1 + b x k 1 + b x k 1 1 + b x k 1 ) = x k 1 1 + 2 b x k 1 But then because of the fact that 1 + 2 b x k > 1 + b x k then we know that x k + 1 = x k 1 1 + 2 b x k 1 < x k 1 1 + b x k 1 = x k

Finally as x 0 = a > a 1 + a b = x 1 as a b R + , then we know that x k > x k + 1 for all k N 0

Next we can prove that all terms are positive because a , b > 0 and all terms are derived from them using operations that maintain positivity so in the induction step it will work. Therefore it is lower bounded by 0 by MCT the limit exists.

Recall that lim n x n = L = lim n x n + 1 = lim n 1 1 x n + b = 1 1 L + b = L 1 + L b We see that this implies 1 + L b = 1 Therefore since b R + we must have that L = 0 .


As an alternative to that, we can find a closed form for x k which allows us to compute the limit directly

Note that in the induction step something interesting occurred, syntactically we could have then replaced x k 1 with x k 2 1 + b x k 2 then following the same simplification steps we would have obtained x k 2 1 + 3 b x k 2 , from this we make the conjecture that x j = a 1 + j b a which we will now prove by showing that for any k N 1 , and any j { 0 , , k } we have x k = x k j 1 + j b x k j

For the base case of j = 1 we see that x k = x k 1 1 + ( 1 ) x k 1 , now suppose it holds true for some j { 1 , , k 1 } and we'll show that it holds true for j + 1 , x k = x k j 1 + j b x k j = x k j 1 1 + b x k j 1 1 + j b ( x k j 1 1 + b x k j 1 ) = x k j 1 1 + b x k j 1 1 + ( j + 1 ) x k j 1 1 + b x k j 1 = x k j 1 1 + ( j + 1 ) b x k j 1

Therefore by finite induction it holds true for all j { 1 , k } specifically for k = j we have x k = a 1 + k b a